Nitrogen-doped porous carbon derived from biomass waste for high-performance supercapacitor. (December 2015) - Ma, Guofu; Yang, Qian; Sun, Kanjun; Peng, Hui; Ran, Feitian; Zhao, Xiaolong; Lei, Ziqiang
Graphical abstract: Highlights: Potato waste residue was utilized to fabricate nitrogen-doped porous carbon. The nitrogen-doped porous carbon contains macropores, mesopores and micropores. The nitrogen-doped porous carbon exhibits high capacitor performance. Abstract: High capacitance property and low cost are the pivotal requirements for practical application of supercapacitor. In this paper, a low cost and high capacitance property nitrogen-doped porous carbon with high specific capacitance is prepared. The as-prepared nitrogen-doped porous carbon employing potato waste residue (PWR) as the carbon source, zinc chloride (ZnCl2 ) as the activating agent and melamine as nitrogen doping agent. The morphology and structure of the carbon materials are studied by scanning electron microscopy (SEM), N2 adsorption/desorption, X-ray diffraction (XRD) and Raman spectra. The surface area of the nitrogen-doped carbon which prepared under 700 °C is found to be 1052 m 2 /g, and the specific capacitance as high as 255 F g −1 in 2 M KOH electrolyte is obtained utilize the carbon as electrode materials. The electrode materials also show excellent cyclability with 93.7% coulombic efficiency at 5 A g −1 current density of for 5000 cycles.